2015
DOI: 10.1088/1674-4926/36/11/114001
|View full text |Cite
|
Sign up to set email alerts
|

Line-edge roughness induced single event transient variation in SOI FinFETs

Abstract: The impact of process induced variation on the response of SOI FinFET to heavy ion irradiation is studied through 3-D TCAD simulation for the first time. When FinFET biased at OFF state configuration (V gs D 0, V ds D V dd / is struck by a heavy ion, the drain collects ionizing charges under the electric field and a current pulse (single event transient, SET) is consequently formed. The results reveal that with the presence of line-edge roughness (LER), which is one of the major variation sources in nano-scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…With the aggressive scaling down of MuGFETs, BTI and HCI are not the only reliability issues in the MuGFET technologies. Reliability topics like electromigration [68,69] , device-todevice variation [70,71] , cycle-to-cycle variation [70] , random telegraph noise [72,73] , dielectric breakdown characteristics [74,75] etc. are also get more severe.…”
Section: Bias Temperature Instability and Hot Carrier Injectionmentioning
confidence: 99%
“…With the aggressive scaling down of MuGFETs, BTI and HCI are not the only reliability issues in the MuGFET technologies. Reliability topics like electromigration [68,69] , device-todevice variation [70,71] , cycle-to-cycle variation [70] , random telegraph noise [72,73] , dielectric breakdown characteristics [74,75] etc. are also get more severe.…”
Section: Bias Temperature Instability and Hot Carrier Injectionmentioning
confidence: 99%
“…When an energetic particle strikes into the sensitive area of FinFET device, single event transient (SET) may be occurred by the diffusion and drift effects 1 3 . Due to the reduced parasitic capacitance from silicon-on- insulator (SOI) technology and the improved tolerance from thin fins, FinFET, with narrow silicon fin, combined with SOI and high k /metal gate stacked technology, brings benefits to radiation effects 2 4 . It was indicated that single event responses of FinFET may be significantly affected by ion hit angular, position and energy, supply voltage, device size and number of fins, technology node, and so on 3 , 5 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many efforts have been devoted to investigate the single event behavior in FinFET technology [6][7][8][9][10][11][12][13]. El-Mamouni et al compare the transient current between bulk and SOI FinFET induced by heavy ion and more collected charges in bulk FinFET are demonstrated [11].…”
Section: Introductionmentioning
confidence: 99%